Optimizing Consistency and Efficiency of Simakip’s Frontend Architecture Through Implementation of Atomic Design Method - Sabrina Qodri Nova; Akhmad Rizal Dzikrillah (Journal of Information System Research (JOSH), 2025)
The Research and Community Service Performance Management System (SIMAKIP) is a centralized website that facilitates UHAMKA academicians to report research and community service activities periodically, by submitting valid research and scientific publications to the ristekdikti website for performance assessment. The problem is that centralized information systems have a wide range of feature complexity, making it important to ensure design consistency and efficiency of interface component development. To address the problem, the implementation of an atomic design approach is used as an innovative method that utilizes reusable modular components in five stages namely atom, molecule, organism, template and page for structured and integrated component development across the application. The purpose of this research is to improve the frontend architecture of SIMAKIP UHAMKA to optimize the performance of the development team and SIMAKIP as a whole, which will contribute to the advancement of research and community service within the academic community. Based on User Acceptance Test (UAT) testing by conducting 10 test cases to 10 participants, it was found that the overall SIMAKIP frontend architecture achieved a percentage of conformity of 95.96% in the Very Good category. These results prove the success of the atomic design approach to the consistency and efficiency of UHAMKA SIMAKIP and have the potential to become a model for other institutions as well as a reference for research in the field of other academic information systems.